The proximate composition and metabolite profiling of sugarcane Saccharum officinarum - Mohd Khairul, Nurul Shafiqa Atikah; Mahyudin, Nor Ainy; Abas, Faridah; Jamaludin, Nur-Syifa'; Mahmud Ab Rashid, Nor Khaizura (Malaysian Society of Applied Biology, 2022)
The transformation of organic by-products into valuable materials has become a necessity and a common practice in the food industry. By-products oftentimes offer low economic value and conferred numerous health benefits. Sugarcane molasses is a waste from the sugar manufacturing process with many valuable compounds. It is known to be rich in nutrients, and the various processing stages might be the cause of the complex nature of sugarcane molasses. Therefore, this study aimed to analyze the proximate composition of sugarcane molasses and to ascertain the sugars and amino acid profile. The result of this study showed that sugarcane molasses is composed of high carbohydrates (75.10±0.7%) and has high sucrose content (38.10±2.4 g). Besides, it comprises several amino acids, namely tyrosine, glysine, proline, glutamic acid, and valine. As the large scale of proximate composition revealed plenty of metabolites present in sugarcane molasses, it can be concluded that this by-product has great nutritional benefits.